(untitled) (Eurasian Medical Research Periodical, 2022)
Breastfeeding burns more calories, hastening the weight loss after pregnancy. It causes the production of the hormone oxytocin, which aids in the uterus’s return to its pre-pregnancy size and may lessen postpartum uterine haemorrhage. Infants get the best nourishment from breast milk. It contains all the vitamins, proteins, and fat that baby needs to develop in a virtually ideal ratio.